Spontaneously separated intermetallic Co3Mo from nanoporous copper as versatile electrocatalysts for highly efficient water splitting - Shi, Hang; Zhou, Yi-Tong; Yao, Rui-Qi; Wan, Wu-Bin; Ge, Xin; Zhang, Wei; Wen, Zi; Lang, Xing-You; Zheng, Wei-Tao; Jiang, Qing (Nature communications, 2020)
Developing robust nonprecious electrocatalysts towards hydrogen/oxygen evolution reactions is crucial for widespread use of electrochemical water splitting in hydrogen production. Here, we report that intermetallic Co 3 Mo spontaneously separated from hierarchical nanoporous copper skeleton shows genuine potential as highly efficient electrocatalysts for alkaline hydrogen/oxygen evolution reactions in virtue of in-situ hydroxylation and electro-oxidation, respectively. The hydroxylated intermetallic Co 3 Mo has an optimal hydrogen-binding energy to facilitate adsorption/desorption of hydrogen intermediates for hydrogen molecules. Associated with high electron/ion transport of bicontinuous nanoporous skeleton, nanoporous copper supported Co 3 Mo electrodes exhibit impressive hydrogen evolution reaction catalysis, with negligible onset overpotential and low Tafel slope (~40 mV dec −1 ) in 1 M KOH, realizing current density of −400 mA cm −2 at overpotential of as low as 96 mV. When coupled to its electro-oxidized derivative that mediates efficiently oxygen evolution reaction, their alkaline electrolyzer operates with a superior overall water-splitting output, outperforming the one assembled with noble-metal-based catalysts. Electrochemical water splitting is an attractive energy conversion technology, but it usually suffers from low efficiency. Here, the authors report intermetallic Co 3 Mo integrated on porous Cu as highly efficient electrocatalysts for alkaline HER/OER due to in-situ hydroxylation and electro-oxidation.